Internalisasi Nilai-Nilai Pendidikan Islam Bagi Narapidana Di Lembaga Pemasyarakatan Kelas II B Kota Pasuruan - Achmat Mubarok (Jurnal Darussalam: Jurnal Pendidikan, Komunikasi dan Pemikiran Hukum Islam, 2016)
Education is essential for humans so that the whole community should be and is entitled to receive education, including prisoners languishing in a holding cell. Implementation of the internalization of the values of Islamic education for inmates in prisons class II B of Pasuruan realized through formal and informal education systems. Implementation of Islamic non-formal education system is realized through lectures, reading and writing the Koran, tambourine art ishari or al-Banjari, Friday prayers in congregation, Khataman Al Qur’an as well as support activities such as Kultum. As for the social interaction with fellow inmates in carrying out various religious activities such as prayer in congregation, pray, discuss the study of jurisprudence together, including in the informal education system. The obstacles encountered in the implementation of the internalization of the values of Islamic religious education in prisons II cities Pasuruan is inadequate capacity, shortage of funds, security personnel, facilities, and limitations of educators